A systematic technique for design of minimum water network - Wan Alwi, Sharifah Rafidah; Abdul Manan, Zainuddin (2006)
Until today, the idea of minimum water design was unknown for urban system even though there has been extensive work on the design and improvement of industrial processes for maximum water recovery. The development of novel systematic techniques to maximise water efficiency in urban buildings represents a shift in the global traditional process engineering paradigm to allow maximum water recovery beyond the frontiers of process industry, into the realm of urban sector. This paper describes the Systematic Hierarchical Approach for Resilient Process Screening (SHARPS) as a new cost-screening tool for design and retrofit of a minimum water network. Guided by the water management hierarchy, SHARPS offers a quick and efficient means to guide and screen inferior process changes and to predict the potential maximum fresh water savings within a desirable investment limits ahead of design. Application of SHARPS technique on Sultan Ismail Mosque in UTM demonstrates substantial water savings potential to satisfy the investment criteria set by the mosque authority with freshwater and wastewater reduction of 97% and 61% respectively for grassroots designs and 71% and 86% respectively for retrofit designs.